Fabrication of designed architectures of Au nanoparticles on solid substrate with printed self-assembled monolayers as templates - Li, S. F. Y. (2012)
This paper provides a convenient method for fabricating architectures of Au nanoparticles on solid substrate,with precise position and density control. Our strategy is to modify Au substrate with self-assembled monolayers (SAMs) terminated with different functional groups. They were chosen to be −CH3/−NH2 or −CH3/−SH according to their affinities to Au nanoparticle. Au nanoparticles assemble selectively on −NH2 or −SH terminated locations, the −NH2 functional group binding electrostatically to the nanoparticles whereas the −SH groups bonding chemically. The SAMs, acting as guiding templates for Au nanoparticles, were fabricated by the microcontact printing (μCP) technique. A patterned or unpatterned SAM was prepared by using patterned or unpatterned poly(dimethyl)siloxane (PDMS) stamp, respectively. The coverage of −CH3 terminated SAM in the contact region is controlled by changing the concentration of “ink” solution for the stamp. After immersing the printed SAM into −SH or −NH2 thiol solutions for 2 h, a mixed SAM with a predetermined coverage of −SH or −NH2 was formed in the contact regions, and a pure −SH or −NH2 SAM was formed in the intervening area. The position and density of nanoparticles on the surface were determined by the distribution of the underlying functional groups.